Penentuan Lokasi Industri Olahan Karet UIKM di Kabupaten Sijunjung - Christina, Shelly; Pigawati, Bitta (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Rubber plantation is one of superior commodity and main-livelihood in community of Sijunjung regency. Rubber product that is managed by community currently is in the form of rubber-slab without further processing because of industrial-processing unavailability in Sijunjung regency. Therefore, it causing long list of market-chain and price that is obtained by farmer become 50-55% of factory-price. The purpose of this research is to determine the location of SME rubber-processing industry in Sijunjung regency. Research methodology implemented here was descriptive-quantitative with scoring and weighted overlay techniques. Analysis was conducted by consideration of conformity variable of SME rubber-processing industry area, accessibility, supporting-facility, value of land, transportation expense, and Urban Planningpolicies in Sijunjung regency. Research finding shows that there are seven districts and 31 villages (Nagari) considered to be compatible for SME rubber-processing industry location. However, the most recommended district from these seven districts that are Kamang Baru in particularly Nagari (village) Takung and Sungai Lansek, because these villages have permission from local government to develop agro-industry and produce majority of rubber-product in Sijunjung regency, and also passing by primary road, electricity and fresh water source.